Effect of the Fly Ash and Cement Type upon the Cement Paste Rheology - Grzeszczyk, Stefania; Lipowski, Grzegorz (Communications - Scientific letters of the University of Zilina, 2002)
In the paper an analysis of the the influence two types of fly ashes on rheological properties of cement pastes with cements containing different amount of C3A is presented. It was stated that a type of fly ash and content of C3A in cement have significant influence upon rhelogical behaviour of cement pastes.